Rhizosphere and Straw Return Interactively Shape Rhizosphere Bacterial Community Composition and Nitrogen Cycling in Paddy Soil - Zhao, Ya-Hui; Wang, Ning; Yu, Meng-Kang; Yu, Jian-Guang; Xue, Li-Hong (Frontiers in Microbiology, 2022)
Rhizosphere is a hotspot of rice-microbe interaction that critically links with soil functions and plant nutrient acquisition. Straw return, as an important agricultural management, has been widely used as a measure to increase soil fertility. However, how roots interact with straw return in structuring rhizosphere communities and nitrogen (N) cycling functions is relatively unexplored. In this study, wheat straw was added into a paddy soil at 1% and 2% w/w, which was used for rice growth. The effects of rhizosphere, straw, and their interaction on soil bacterial community composition and N-cycling gene abundances were assessed at rice maturity stage. We observed that rhizosphere significantly altered the bacterial community composition for the soil by comparing bulk and rhizosphere of control treatment without straw addition. Quantification of six nitrogen-cycling genes (nifH, bacterial amoA, archaeal amoA, nirK, nirS, and nosZ) revealed that rhizosphere was enriched in AOA, nirK and nosZ genes abundance, but significantly decreased AOB gene abundance. By comparing bulk soils of control and straw treatments, the shift in bacterial community composition and the decrease in the abundance of AOA, AOB, nirS and nosZ were observed, which was attributed to sole straw effects. For rhizosphere soils, straw amendment significantly changed bacterial community composition and resulted the increase in nifH gene abundance, and the decrease in abundance of AOA, AOB, nirK, nirS and nosZ, indicating the interaction effects of straw and rhizosphere. Compared to sole straw or rhizosphere, the interaction of straw and rhizosphere reshaped microbial community at a higher extent, as reflected by high numbers of genera being affected by the interaction of straw and rhizosphere compared to straw or rhizosphere effect, resulting from the increase in nifH gene and the decrease in nirK gene. In conclusion, this study illustrated how rhizosphere interacts with straw return practices to shape rhizosphere microbial community composition and nitrogen-cycling process.